Achievement Motivation for Work Effectively of Teachers in Catholic Affiliated School - Chanluechai, Tanakan (Saengtham College Journal, 2025)
Achievement Motivation is an internal desire or aspiration that drives an individual to work efficiently and effectively, emphasizing the accomplishment of goals and the continuous improvement of work. Those with achievement motivation tend to exhibit behaviors marked by dedication, persistence, enthusiasm in their work, a sense of responsibility towards their tasks, and the determination to overcome obstacles with the hope of achieving success rather than fearing failure. This article aims to explore the concept and theory of Achievement Motivation, its significance, development, and characteristics in individuals. It is believed that Achievement Motivation serves as a driving force that enables individual teachers in catholic affiliated school to achieve high-quality work outcomes.